Use of end-of-life tires for the production of a waterproofing agent as a strategy to promote the circular economy - Valentina Salcedo-Mojica; Jaime Arturo-Calvache; Cristina Ramírez-Meneses (Dyna)
This paper develops a formulation to produce a laboratory-scale waterproofing for exterior walls and roofs using recycled tires. It begins by identifying its chemical composition using Fourier transform infrared spectroscopy and selects a technology using the ELECTRE method. It uses a reticular simplex mixing design of experiments to adjust the resin proportions according to their mechanical properties. In addition, it evaluates the critical pigment volume content and parameters such as water absorption, permeability, total solids content and mechanical properties for quality assurance. Acrylic emulsions were found to be favorable in cost, application, safety, and efficiency; the flexible resin offers better elongation and the rigid one better tensile strength, with less than 10% tire reducing porosity. The results support the competitiveness of the product and confirm the effective use of recycled tires in waterproofing, offering a favorable and functional approach to construction.